(untitled) - Ito, Takatoshi (Cambridge, 1992)
Contents: A comparative perspective and an analytic approach grounded in mainstream economics distinguish this broad, accessible introduction to the Japanese economy. Throughout, Ito utilizes standard economic concepts in comparing Japan with the United States in terms of economic performances, underlying institutions, and government policies.Referring to cultural factors where appropriate, Ito subjects the basic facts about the Japanese economy to modern theoretical and empirical scrutiny, discussing macroeconomic growth, business cycles, monetary and fiscal policies, industrial structures and policies, the labor market, saving and investment, and international trade and finance.
Keywords: Economic conditions,Điều kiện kinh tế; Japan,Nhật Bản